ERGONOMIC ANALYSIS OF CLASSROOM FURNITURE IN A NIGERIAN UNIVERSITY (Nigerian Journal of Technology, 2018)
In most underdeveloped and developing countries, the anthropometric dimensions of users are not deployed in classroom furniture design. This has severe health as well as learning implications. The aim of this study was to determine the ergonomic suitability of classroom furniture at the Federal University of Technology, Akure, Nigeria. 261 (133 males and 128 females) randomly selected students participated in the study. Their anthropometric measures were taken after fully explaining the purpose and procedure of the measurements and obtaining an informed consent from each student. The dimensions of the furniture in all the selected lecture venues were also taken. The level of match/mismatch between the anthropometric measures of the students and classroom furniture was afterwards determined using some criterion equations. The result of the study showed a substantial level of mismatch between the anthropometric measures of students and the dimensions of the furniture available to them for use in lecture venues. In all, 31.8% and 37.2% of the participants in the study used seats that are too high and too low respectively for their anthropometric measures while 18.4% and 50.6% of the participants used seats that are too deep and too shallow respectively for their anthropometric measures. The study revealed that 90% of all the participants used desks that were too high, 2% used desks that were too low and only 7% used desks with heights that fit their anthropometric measures. Only at one lecture venue was a non-zero score (5.5%) returned for a combined seat height – seat depth analysis. The study evidently suggests that many students use unfit classroom furniture which are not conducive for learning. http://dx.doi.org/10.4314/njt.v37i4.40